The Role Of Future Work Self As Moderator Between Career Anxiety And Career Decision Making Difficulty - Raditya, Dewa Gede Nata; Salim, Rose Mini Agoes (Jurnal Pendidikan Indonesia, 2025)
The characteristics of Gen Z, who are prone to anxiety, will potentially cause them to have difficulty in determining their first career. Anxiety has a strong reciprocal relationship with difficulty in decision-making. This study aims to understand the role of having a Future Work Self or a clear career self-image in the relationship between career anxiety and difficulty in career decision-making. The study used a quantitative approach with moderation analysis. The participant sampling used random sampling on the population of Generation Z students in Indonesia. A total of 157 participants took part in this study. The data collection method employed a questionnaire, which was analysed using moderation analysis to determine the interaction between variables. The results showed that Future Work Self correlated negatively with the level of difficulty in career decision-making; however, the moderation analysis revealed that Future Work Self did not play a significant role as a moderator. The research findings indicate that Gen Z students can experience anxiety and struggle with decision-making despite having a clear career self-image. This study concludes that future work self plays a significant moderator in the relationship between career anxiety and difficulty in career decision-making. The stronger an individual's image of themselves in the future in the context of work, the lower the negative impact of career anxiety on their ability to make effective career decisions. This research offers implications for campus policymakers, particularly career centres, to provide training on managing career anxiety.